In situ minority carrier lifetime via fast modulated photoluminescence - Poplawski Mateusz; Silva François; Vanel Jean-Charles; Roca i Cabarrocas Pere (EPJ Photovoltaics, 2023)
Modulated photoluminescence (MPL) is a powerful technique for determining the effective minority carrier lifetime (τeff) of semiconductor materials and devices. MPL is based on the measurement of phase shifts between two sinusoidal waves (minimal amplitude excitation; and PL signal). In particular, in situ τeff has been proven to be an effective measurement at showing changes within a plasma-enhanced chemical vapor deposition reactor during fabrication of c-Si solar cells. However, the required time for a single measurement, using the previous method, was 40 s. In this paper a new input signal is proposed, called Dolphin's Wave, providing a method for decreasing the required measurement period to under 2 s, using superposition, frequency sweeps, and wavelets.